The The Paratactic and Hypotactic Constructions in Research Article Abstracts at 2018 ISET Proceedings - Sarip, Sri Kurnia; Fitriati, Sri Wuli; Rukmini, Dwi (Universitas Negeri Semarang, 2020)
The present study was a part of larger research aimed at analysing the research article abstracts taken from International Conference on Science and Education and Technology 2018 (ISET 2018). This study was descriptive study under SFL analysis in research article abstracts at 2018 ISET realized from 170 clause complexes. Under a SFL theory, the data were collected through retrieving twenty relevant article abstracts on the International Conference on Science and Education and Technology 2018 (ISET 2018). The article abstracts are analysed using the framewok of systemic functional linguistic as suggested by Halliday & Matthiessen (2014). However, in this study the writer employs the taxis sytems which covers elaboration, extension, and enhancement. Besides, logico-semantic relation is also analysed which covers projection and expansion. The findings reveal that there are 81 clause complexes of parataxis which are realised 47%, afterwards, there are 35 clause complexes of hypotaxis which are realised 20.5%. Hence, the researchers is more using parataxis then hypotaxis. Bassed on the findings, it is recommended that English teacher can apply clause constructions to encourage the English learners to think critically. After being able to implement their critical thinking, the English learners are hoped to be able to read critically. Through having critical reading, they are suggested to be able to evaluate both their works and the other works as the main purpose in learning systemic functional linguistics.